Great potency of seaweed waste biomass from the carrageenan industry for bioethanol production by peracetic acid–ionic liquid pretreatment. (October 2015) - Uju,; Wijayanta, Agung Tri; Goto, Masahiro; Kamiya, Noriho
Abstract: Seaweed waste biomass from the carrageenan industry (SWBC) is a potential biomass feedstock for producing sustainable biofuel because it increases the product value and reduces the pollutant risk. Peracetic acid (PAA) followed by ionic liquid (IL) pretreatment has been used to increase the enzymatic saccharification of pretreated SWBC. The SWBC cellulose content was comparable with that of terrestrial biomasses. PAA + 1-hexylpyridinium chloride ([Hpy][Cl]), and PAA + 1-ethyl-3-methylimidazolium diethylphosphate ([Emim][DEP]) pretreatments produced saccharide and unknown oligosaccharide fractions in regenerated water (∼4–6% SWBC cellulose content). For 48 h of saccharification, the untreated SWBC and the SWBC pretreated using PAA followed by [Hpy][Cl], [Emim][DEP] or 1-ethyl-3-methylimidazole acetate ([Emim][OAc]) produced cellulose conversions of 77, 91, 84 and 62%, respectively. The untreated SWBC had a high cellulose conversion, which may be caused by the low lignin and hemicellulose contents of the SWBC. PAA + IL pretreatment could yield pretreated SWBCs with more amorphous cellulose structures, which lead to an almost-complete cellulose conversion. Highlights: Waste biomass from the carrageenan industry has great potency for biofuel feedstock. The untreated biomass had 77% cellulose conversion for 48 h enzymatic saccharification. Combination pretreatments of peracetic acid–ionic liquid were carried out. The pretreatments released 4–6% of saccharides in the regenerated water. The pretreated biomasses resulted in almost complete cellulose conversion (84–91%).